Collaboration between general practitioners and social workers: a scoping review. Issue 6 (3rd June 2022) - Löwe, Cornelia; Mark, Patrick; Sommer, Samira; Weltermann, Birgitta
Abstract : Objectives: Aim of the study is to present an overview of collaboration structures and processes between general practitioners and social workers, the target groups addressed as well the quality of available scientific literature. Design: A scoping review following the guidelines of the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews). Included sources and articles: According to a pre-published protocol, three databases (PubMed, Web of Science, DZI SoLit) were searched using the participant-concept-context framework. The searches were performed on 21 January 2021 and on 10 August 2021. Literature written in English and German since the year 2000 was included. Two independent researchers screened all abstracts for collaboration between general practitioners and social workers. Articles selected were analysed regarding structures, processes, outcomes, effectiveness and patient target groups. Results: A total of 72 articles from 17 countries were identified. Collaborative structures and their routine differ markedly between healthcare systems: 36 publications present collaboration structures and 33 articles allow an insight into the processual routines. For all quantitative studies, a level of evidence was assigned. Various measurements are used to determine the effectiveness of collaborations, for example, hospital admissions and professionals' job satisfaction. Case management as person-centred care for defined patient groups is a central aspect of all identified collaborations between general practitioners and social workers. Conclusion: This scoping review showed evidence for benefits on behalf of patients, professionals and healthcare systems by collaborations between general practitioners and social workers, yet more rigorous research is needed to better understand the impact of these collaborations. Trial registration number: www.osf.io/w673q .